2014
DOI: 10.1074/jbc.m113.537043
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and Extracellular Carbonic Anhydrases Cooperate Non-enzymatically to Enhance Activity of Monocarboxylate Transporters

Abstract: Background: Monocarboxylate transporters (MCTs) mediate the shuttling of high-energy metabolites between different cells. Results: Transport activity of MCTs is augmented by intracellular and extracellular carbonic anhydrases (CAs). Conclusion: Intracellular and extracellular CAs can work in concert to ensure rapid shuttling of metabolites across the cell membrane. Significance: CAs play a pivotal role as regulators of metabolite transport in different tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 52 publications
2
60
2
1
Order By: Relevance
“…For a more comprehensive review on bicarbonate transport metabolons see Refs. 39 -41. Using heterologous protein expression in Xenopus oocytes, we have recently reported that CAII enhances transport activity of MCT1 and MCT4, while leaving transport activity of MCT2 unaffected (42)(43)(44)(45)(46). In contrast to the transport metabolons described so far, this interaction is independent of CAII catalytic activity but is mediated by an intramolecular H ϩ shuttle within the enzyme (47,48).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…For a more comprehensive review on bicarbonate transport metabolons see Refs. 39 -41. Using heterologous protein expression in Xenopus oocytes, we have recently reported that CAII enhances transport activity of MCT1 and MCT4, while leaving transport activity of MCT2 unaffected (42)(43)(44)(45)(46). In contrast to the transport metabolons described so far, this interaction is independent of CAII catalytic activity but is mediated by an intramolecular H ϩ shuttle within the enzyme (47,48).…”
mentioning
confidence: 63%
“…We have previously shown that CAII facilitates transport activity of MCT1, but not MCT2, when the proteins are heterologously expressed in Xenopus oocytes (42,43,(45)(46)(47)(48)(49). Facilitation of MCT1 transport function has been found to be independent of the catalytic activity of the enzyme (42, 43) but required both the intramolecular H ϩ shuttle of CAII (CAIIHis 64 ) (48) and the CAII-binding site 489 EEE in the C terminus of MCT1 (49).…”
Section: Discussionmentioning
confidence: 99%
“…CA is known to inhibit MCT4, preventing monocarboxylate uptake and therefore inhibiting extracellular lactate transport (24). In addition, IS may block lactate transport via inhibition of CA9 activity (4).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of production can increase 50-fold if either glucose or glycogen is required to generate ATP in the absence of oxygen [57]. Lactate is transported out of the cell via monocarboxylate transporters (MCT) in an electroneutral transport mode of 1 H + : 1 Lactate [58]. H + transport system under conditions of exclusively aerobic metabolism is used by the cell to maintain a facilitation of CO 2 diffusion, whereas under conditions of dominating anaerobic glycolysis and low intracellular pH, it is mainly used to transport H + along with the lactate anion through the monocarboxylate transporters (MCT), a prerequisite for the elimination of lactic acid from the cell.…”
Section: Discussionmentioning
confidence: 99%